Niat Konsumen Dalam Pembelian Makanan Sehat Di Dailee Healthy Club Malang Dengan Pendekatan Theory Of Planned Behaviour Dan Health Consciousness - Siagian, Samantha Naomi Sonata; Faizal, Febriananda; Pintakami, Lintar Brillian (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
The last few years the community is aware that body health is important and healthy food has become the center of attention for consumers who are aware of the health of the body, especially to avoid dangerous diseases. However, although health awareness in the community increases on healthy eating patterns, there are still problems in encouraging people to choose and buy healthy food. Changes in consumer behavior certainly have an impact on consumer intention in making purchases that require certain considerations and information. This study aims to analyze the influence of attitudes, subjective norms, behavior control, and health consciousness on the intention to buy healthy food. This study uses a quantitative approach with the structural equation model-partial Least Square (SEM-PLS) Software Warppls 8.0 method. The sampling technique uses simple random salmpling with a total of 105 samples of research samples. The results of the data analyst show that the four variables, namely Attitude (X1), Subjective Norms (X2), Behavior Control Perceptions (X3), and Health Consciousness (X4) have a positive and significant effect on the Purchase Intention (Y) of healthy food. The managerial implication that can be applied by business actors is to pay more attention to the marketing system to focus on the promotion of Word of Mouth (WOM) as part of the marketing communication target, as well as increasing the added value or advantage of product quality.